Influences of the ambient temperature, degradation effect and usage habits over the energy consumption of domestic refrigerators in Brazil (Research, Society and Development, 2022)
Considering the relevance of the consumption of domestic refrigerators in the Brazilian residential sector, representing about 30% of the sectorial consumption, studies of factors that influence this consumption, such as ambient temperature, age of equipment and usage habits, are of great importance to a greater understanding of these effects and, thus, to promote better energy strategies for the country. In this sense, the present study evaluates the impacts of ambient temperature, age of the equipment and habits of use in the consumption of domestic refrigerators, based on theoretical models and laboratory tests. The laboratories assays, adhering to theoretical models, showed that the environment temperature can influence the consumption of refrigerators up to 50% less (taking into account the south region temperature), when comparing to the value that are labeled by PBE/INMETRO. When the usage habits are assayed, it was verified that the consumption of the refrigerator could be increased in up to 53%, depending the frequency of door opening.